COLLABORATIVE POLICY-MAKING, LAW STUDENTS, AND ACCESS TO JUSTICE: THE REWARDS OF DESTABILIZING INSTITUTIONAL PATTERNS - Lowenberger, Brea; Keet, Michaela; Anderson, Janelle (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
Heightened concerns and dialogue about access to justice have infused the law school setting in Saskatchewan and, to varying degrees, across the country. If there ever were a time to approach social justice reform differently – to upset traditional parameters around decision making and step around older hierarchies for input and design – it would be now. This article describes the Dean’s Forum on Dispute Resolution and Access to Justice (colloquially known as the Dean’s Forum) as a platform for genuine student engagement in the development of public policy in this important area. We offer our combined reflections, gathered inside our “teaching team,” about the unique pedagogical features of our experiment and its challenges. As we continue to grow with the project, we offer this Saskatchewan story as one example of institutional collaboration in a quickly evolving educational and social policy landscape.